2016
DOI: 10.1128/jvi.00492-16
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of Antiretroviral Therapy Restores CD4 + T Memory Stem Cell Homeostasis in Simian Immunodeficiency Virus-Infected Macaques

Abstract: Treatment of human immunodeficiency virus (HIV) infection with antiretroviral therapy (ART) has significantly improved prognosis. Unfortunately, interruption of ART almost invariably results in viral rebound, attributed to a pool of long-lived, latently infected cells. Based on their longevity and proliferative potential, CD4؉ T memory stem cells (T SCM ) have been proposed as an important site of HIV persistence. In a previous study, we found that in simian immunodeficiency virus (SIV)-infected rhesus macaque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 24 publications
4
15
0
Order By: Relevance
“…Following ART initiation at week 5 after infection, we observed a 2 to 3 log reduction in plasma viral loads within 2 weeks and levels below the limit of detection of our assay (60 copies/ml plasma) after 4 to 22 weeks of treatment. Consistent with prior studies of SIV infection in adult RMs (17,23), the absolute number of peripheral CD4 ϩ T cells was significantly decreased following infection (1,644 Ϯ 203 preinfection versus 916 Ϯ 101 pre-ART; P ϭ 0.006) ( Fig. 1B) and was partially restored on ART (916 Ϯ 101 pre-ART versus 1,441 Ϯ 81 on ART; P ϭ 0.0003) (Fig.…”
Section: Resultssupporting
confidence: 89%
“…Following ART initiation at week 5 after infection, we observed a 2 to 3 log reduction in plasma viral loads within 2 weeks and levels below the limit of detection of our assay (60 copies/ml plasma) after 4 to 22 weeks of treatment. Consistent with prior studies of SIV infection in adult RMs (17,23), the absolute number of peripheral CD4 ϩ T cells was significantly decreased following infection (1,644 Ϯ 203 preinfection versus 916 Ϯ 101 pre-ART; P ϭ 0.006) ( Fig. 1B) and was partially restored on ART (916 Ϯ 101 pre-ART versus 1,441 Ϯ 81 on ART; P ϭ 0.0003) (Fig.…”
Section: Resultssupporting
confidence: 89%
“…The main findings of the current study are that administration of ART in SIV-infected SMs was well tolerated overall and resulted in a rapid decline of viremia to levels below the limit of detection of our standard assay in all but one treated animal. The level of viremia decline observed in the current study is comparable overall to what we observed in similar studies conducted on SIV-infected RMs (19,44). In addition, we found that ART initiation was followed by an increase in the percentage of CD4 ϩ T CM cells in peripheral blood, an increase of CD4 ϩ T cells in the rectal mucosa, and a decline in the levels of activated CD8 ϩ HLA-DR ϩ T cells in both blood and the rectum.…”
Section: Discussionsupporting
confidence: 76%
“…These cells may represent a "stemlike" population of T cells, which are described as an early differentiating memory phenotype, distinct from naïve T cells, that are long-lived and possess a unique ability to proliferate and self-renew (Ahmed et al, 2016;Caccamo et al, 2018;Gattinoni et al, 2011). Similar cells have been reported in human and animal models of viral infection (Cartwright et al, 2016;Fuertes Marraco et al, 2015) and tumors (Ando et al, 2020;Brummelman et al, 2018;Wu et al, 2019), and in humans with Chagas disease (Mateus et al, 2015). In the tumor microenvironment, stem-like T cells have been described as expressing inhibitory receptors such as PD-1 (Siddiqui et al, 2019).…”
Section: Stem-like T Cell Function In Tb Lung Granulomasmentioning
confidence: 73%